Fruit quality and productivity of pineapple under different planting densities and irrigation levels - Souza, Olegário Pinheiro de; Teodoro, Reges Eduardo Franco; Melo, Berildo de; Torres, Jose Luiz Rodrigues (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of different planting densities and two irrigation levels on the fruit quality and productivity of pineapple (Ananas comosus (L.) Merril). A randomized block experimental design was used with six planting densities and two irrigation levels, with five replicates. Fruit weight, firmness, and juice yield were evaluated. The diameters of the fruit and of the stalk were also measured. The primary fruit, ratoon fruit, and the total fruit yield were calculated. The increase in planting density caused a decrease in the average fruit weight, diameter of the fruit and of the stalk, juice yield, and primary crop. However, plant density did not affect fruit firmness. The higher irrigation rate did not influence the fruit weight average, the diameter of the fruit and of the stem, or the primary crop, but did cause a decrease in fruit firmness and juice yield in the 35,714 and 71,429 plants ha-1 populations. The total fruit productivity increased with plant density and was not influenced by irrigation rate.
Keywords: Ananas comosus; plant density; evapotranspiration